2020
DOI: 10.1021/acs.nanolett.0c02319
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of Drug-Carrier Optimization: Controlling Stimuli Sensitivity via Nanoparticle Hydrophobicity through Drug Loading

Abstract: Interactions between drug molecules, nanocarrier components, and surrounding media influence the properties and therapeutic efficacies of nanomedicines. In this study, we investigate the role that reversible covalent loading of a hydrophobic drug exerts on intra-nanoparticle physical properties and explore the utility of this payload control strategy for tuning the access of active agents and, thereby, the stimuli sensitivity of smart nanomaterials. Glutathione sensitivity was controlled via altering the degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…This might contribute to the formation of large agglomerates, in which DOX in the polymer chain forms a hydrophobic core via intra- and intermolecular hydrophobic interactions under static conditions, as described above. Lin et al recently reported that aqueous accessibility to the hydrophobic drug-loaded moiety would decrease and limit the diffusion of water and water-soluble molecules, which would reduce the responsiveness to stimuli that could prompt the release of drugs . Even though the hydrazone bond would be cleaved under acidic conditions in the system of LP–DOX as well, the diffusion of the released DOX must be suppressed in the restricted space of the hydrophobic core.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This might contribute to the formation of large agglomerates, in which DOX in the polymer chain forms a hydrophobic core via intra- and intermolecular hydrophobic interactions under static conditions, as described above. Lin et al recently reported that aqueous accessibility to the hydrophobic drug-loaded moiety would decrease and limit the diffusion of water and water-soluble molecules, which would reduce the responsiveness to stimuli that could prompt the release of drugs . Even though the hydrazone bond would be cleaved under acidic conditions in the system of LP–DOX as well, the diffusion of the released DOX must be suppressed in the restricted space of the hydrophobic core.…”
Section: Resultsmentioning
confidence: 99%
“…Lin et al recently reported that aqueous accessibility to the hydrophobic drug-loaded moiety would decrease and limit the diffusion of water and watersoluble molecules, which would reduce the responsiveness to stimuli that could prompt the release of drugs. 56 Even though the hydrazone bond would be cleaved under acidic conditions in the system of LP−DOX as well, the diffusion of the released DOX must be suppressed in the restricted space of the hydrophobic core. This might also provide an opportunity for the hydrazone bond to re-form between DOX and the polymer chain, resulting in the suppression of the DOX release.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Naturally sourced sugar-based polymers are promising alternatives to petroleum-based materials for various functional and structural applications, due to their high abundance, structural diversities, and degradation potential. To date, organocatalytic ring-opening polymerizations (ROPs) of cyclic carbonate monomers have been demonstrated as low toxic, metal-free, and mild pathways to prepare sugar-based polycarbonates with predeterminable molar masses and narrow dispersities. However, there are few reports on the regioregularity between sugar monomer repeat units. Buchard and co-workers studied the 1,5,7-triazabicyclo[4.4.0]­dec-5-ene (TBD)-catalyzed ROP of six-membered d -mannose-based 4,6-cyclic carbonates .…”
Section: Introductionmentioning
confidence: 99%
“…These delivery systems are specifically designed to overcome the shortcomings associated with traditional drug delivery mechanisms, including poor biodistribution, high toxicity, and poor sensitivity. 1,2 By using modified magnetic particles as drug carriers and enriching magnetic drug particles in the lesion, the loaded drug is released in a controlled manner to achieve targeted therapy. Thus, the magnetically targeted drug delivery system achieves the four-fold objective of synergism, toxicity reduction, controlled release, and gradual release.…”
Section: Introductionmentioning
confidence: 99%